2010
DOI: 10.1248/jhs.56.215
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subacute Effects of Dexamethasone on the Number of White Blood Cells in Rats

Abstract: The purpose of this study was to elucidate the effects of dexamethasone, a synthetic glucocorticoid, on the immune system by analyzing the number of white blood cells (WBCs) over the course of hours and days of dexamethasone administration. Dexamethasone was given as either a single dosage [1.0 mg/kg body weight (BW); subcutaneous injection (s.c.)] or as a daily dosage (1.0 mg/kg BW per day; s.c.) for 10 days for the hourly and daily assessment of changes in the number of white blood cells, respectively. A sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 28 publications
7
15
0
Order By: Relevance
“…Our recent observations also showed that a single administration of dexamethasone (dose = 1.0 mg/kg body weight) markedly decreased the number of lymphocytes with a nadir at 8 hr of post s.c. injection, and the number of lymphocytes recovered to the normal levels at 24 hr of post s.c. injection. 22) In the present study, we showed that administration of AITC for 4 days increased markedly plasma corticostrone concentrations to 5.4-6.0 times, as compared with the control values (Fig. 5).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Our recent observations also showed that a single administration of dexamethasone (dose = 1.0 mg/kg body weight) markedly decreased the number of lymphocytes with a nadir at 8 hr of post s.c. injection, and the number of lymphocytes recovered to the normal levels at 24 hr of post s.c. injection. 22) In the present study, we showed that administration of AITC for 4 days increased markedly plasma corticostrone concentrations to 5.4-6.0 times, as compared with the control values (Fig. 5).…”
Section: Discussionsupporting
confidence: 63%
“…The experiment was performed with the least possible pain of discomfort to the animals. [11][12][13][20][21][22] Administration of AITC to Rats --AITC (purity 95%; Wako Pure Chem. Ind., Osaka, Japan) was dissolved in 2% ethanol and then added 10% Tween 80 and 0.9% NaCl as a vehicle to obtain 0.5% and 1.0% of AITC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, increased plasma glucocorticoid levels cause a significant reduction in the circulating number of lymphocytes and monocytes (26). In fact, acute administration of corticosterone and dexamethasone reduced the circulating number of these cells (16,28). Furthermore, glucocorticoids are known to act more sensitively to B-lymphocytes than T-lymphocytes and NK cells (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, the overall responses of the number of white blood cells, and plasma zinc and corticosterone levels in the recovery from dietary zinc-deficiency are still unknown. These questions are of critical importance to understanding of the distribution of white blood cells as an index of the immune-responses of the body defense system (7)(8)(9)(10)(11)(12). In the present study, therefore, we studied the effects of the recovery from dietary zinc-deficiency on the distribution of the number of total white blood cells (WBCs), neutrophils, eosinophils, and basophils, and plasma zinc and corticosterone concentrations in weanling male rats.…”
mentioning
confidence: 98%